Rapid diagnosis of fatal Nocardia kroppenstedtii bacteremic pneumonia and empyema thoracis by next-generation sequencing: a case report - Xing, Fanfan; Xia, Yao; Lu, Qianyun; Lo, Simon K. F.; Lau, Susanna K. P.; Woo, Patrick C. Y. (Frontiers in Medicine, 2023)
Nocardia species do not replicate as rapidly as other pyogenic bacteria and nocardial infections can be highly fatal, particularly in immunocompromised patients. Here, we present the first report of fatal Nocardia kroppenstedtii bacteremic pneumonia and empyema thoracis diagnosed by next-generation sequencing (NGS) using the Oxford Nanopore Technologies' MinION device. The bacterium was not identified by matrix-assisted laser desorption ionization-time of flight mass spectrometry. Due to its low equipment cost, short turn-around-time, and portable size, the Oxford Nanopore Technologies' MinION device is a useful platform for NGS in routine clinical microbiology laboratories.